Sol–gel synthesis of TiO2 doped with chromium: photocatalytic degradation of tartrazine - Ana E. Cardozo; Elsa M. Farfán Torres; Graciela V. Morales; Edgardo L. Sham (Academia Materials Science)
Photocatalysis is an advanced oxidation method that allows the removal of aqueous pollutants of different origins. However, its application on an industrial scale is limited due to the requirement of excitation sources in UV frequency. For this reason, it is important to develop photocatalytic materials capable of working under visible radiation in photodegradation processes. This study analyzes the synthesis of TiO2 nanoparticles, using a new sol–gel route in a nonpolar dissolvent and its modification by doping with different chromium VI ion concentrations: 0.5, 1.0, and 1.5% w/w. A novel modification of this synthesis technique is reported, in which a nonpolar solvent, C6H12, is used to control the hydrolysis reactions of the titania precursor. Similarly, the use of ammonium chromate, (NH4)2CrO4, introduced by means of the impregnation-by-moisture-incipient technique, is proposed as a precursor of Cr dispersed in the TiO2 network, together with the study of the influence of chromium content on the photocatalytic activity of solids. The solids obtained by this technique were heat-treated at 400°C and characterized by Fourier Transform Infrared Spectroscopy (FTIR), Raman Spectroscopy, Diffuse Reflectance Spectroscopy, X-Ray Diffraction (XRD), N2 Sorptometry, and Zeta Potential. Doping of titania with chromium stabilizes the crystalline phases of anatase and brookite. In addition, the introduction of chromium (VI) ions tends to reduce the average size of the particles, increasing the specific surface area and favoring the development of a mesoporous structure. It also decreases the forbidden band (Eg) and increases the absorption of radiation in the visible light range.